Analisis Manajemen Pendidik Raudlatul Athfal di Tinjau dari Pengembangan Karir di Kabupaten Pekalongan - Mazidah, Umi; Suminar, Tri; Diana, Diana (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
This study aims to analyze the management of RA Educators, as well as describe the analysis of RA educator management in career development in Pekalongan Regency, the study uses a sequential mixed methods approach with a sequential exploratory design and qualitative data collection techniques with interviews and observations at RA Muslimat Al Utsmani Kajen, RA Muslimat NU Kebonrowopucang Karangadadap and RA Muslimat NU Pajomblangan Kedungwuni and literature studies. While the quantitative data uses a questionnaire with cluster sampling techniques, and based on the region also uses Simple Random Sampling as many as 17 RA heads and RA teachers with a population of 15% of the total 109 RAs in Pekalongan Regency for the reasons 1) accredited, 2) the number of educators with linearity of diplomas during recruitment and 3) the number of teachers who have not been certified. As for analyzing the data using data reduction, normality test, multicollinearity test and heteroscedasticity test, this study resulted in an analysis of the relationship between educator management carried out by the head of RA in developing his educator career by 75.2% with educator management including planning teacher recruitment, holding IHT, involving teachers and implementing workshops and training greatly influencing teacher career development.